SENGKETA WARIS DAN VALIDITAS DOKUMEN DALAM STUDI KASUS SHANDY SUSANTO MENURUT TINJAUAN HUKUM PERDATA DAN TRADISI TIONGHOA - Nisrina Baidha Nibras; Najmi Fauziatus Salma; Muhammad Yazid Attala; Putra Farhan Mulyadi; Muhammad Yoviansyah; Agus Iryana (Causa: Jurnal Hukum dan Kewarganegaraan, 2024)
This study examines the inheritance case of Shandy Susanto from the perspective of civil law and Chinese traditions, reflecting the conflict between the patriarchal Chinese customary law and Indonesian civil law, which emphasizes gender equality. Using a qualitative method and a literature review approach, the study finds that the Indonesian Civil Code recognizes equal rights for adopted and biological children, while Chinese customary law tends to prioritize male heirs. This case highlights the importance of valid documents, such as notarial deeds and the Certificate of Inheritance, in determining heir status amidst allegations of document falsification that can lead to conflicts. Amid Indonesia’s pluralistic inheritance legal system, the decision of the Banten High Court, which designated Shandy Susanto as the sole heir, reinforces the supremacy of civil law. The study emphasizes the importance of harmonizing customary and national laws.